Asymmetry Matters: Structure Elucidation and Application Potential of Solution-Processed Monoalkylated BTBT Thin Films - Hawly, Tim; Johnson, Manuel; Zhao, Baolin; Wu, Mingjian; Späth, Andreas; Streller, Fabian; Nickles Jäkel, Hannah; Halik, Marcus; Spiecker, Erdmann; Watts, Benjamin; Nefedov, Alexei; Fink, Rainer (ACS Applied Electronic Materials, 2022)
Two-dimensionally (2D) extended thin films of p-type organic semiconductor C13-BTBT (BTBT = [1]benzothieno[3,2-b]-[1]benzothiophene) were fabricated via self-controlled growth at the liquid-liquid interface. Depicting a compound class originally developed for further functionalization and subsequent realization of self-assembled monolayers (SAMs), the potent BTBT core unit commonly excels in high-quality structure formation as well as charge-transport characteristics. Utilizing a manifold spectromicroscopic toolbox, we observe extraordinarily crystalline C13-BTBT films with an upright standing configuration of the backbone unit accounting for superior intermolecular orbital overlap. The well-defined morphology and internal structure of the film are being underpinned by charge-transport parameters that are in the range of comparable organic electronic devices based on bisubstituted BTBT films from the same processing technique. The inherently favorable membrane-like bilayer molecular arrangement is confirmed by unambiguous representation of the unit cell as derived from electron tomography.
CRIS-Team WoS Importer:2023-01-27